Tirzepatide (Mounjaro)-induced acute pancreatitis and ketoacidosis in an adult nondiabetic patient - Asma Ali Sallam; Bdoor Attaulla Alenezi; Muneerah M. Albugami (Saudi Journal for Health Sciences)
Tirzepatide (Mounjaro) is a new medication approved for type 2 diabetes and obesity treatment. It works by activating the receptors for both glucose-dependent insulinotropic peptide and glucagon-like peptide-1. Side effects due to tirzepatide are typically gastrointestinal in nature and self-resolving within a few days. Severe hypoglycemia, acute pancreatitis, or gallbladder disease are uncommon. We present the case of an adult nondiabetic patient who developed acute pancreatitis and ketoacidosis due to tirzepatide. Both are uncommon and serious adverse events of tirzepatide. Physicians should be aware of serious side effects due to tirzepatide as many nondiabetic patients take tirzepatide over the counter for weight loss. Tirzepatide should be prescribed under medical supervision.